(untitled) (American Journal of Islam and Society, 2004)
As the Muslim world searches for the right formula for reform, scholars and intellectuals are invited to study Islamic reform movements and the conditions that made their successes possible. In this context, Najd before the Salafi Reform Movement is a timely contribution to the literature on social conditions of reform in Muslim societies. The author correctly notes that pre-Salafi Najd (central Arabia) was neither a center of religious learning nor the site of large urban communities, which might be expected to produce a reform movement of a size and significance of the Salafi movement. Nevertheless, the Salafi movement managed to establish a strong state that unified Arabia and imposed peace and order on its people for the first time since the period of the early caliphs (pp. 1-2). This book, originally a Ph.D. dissertation, seeks to solve this puzzle. A six-page bibliography and a thirteen-page index are suffixed, along with several maps and tables, and both the Hijri and the Gregorian calendars are used to mark the general time periods. This book is particularly useful for students of history, sociology, anthropology, or genealogy in an earlymodern context, such as that of Najd between the mid-ninth/fifteenth and mid-twelfth/eighteenth centuries. The author argues that nomadic migration and settlement; the growth of a sedentary population, as well as migration and resettlement; and the growth of religious learning combined to create a new Najdi society that produced the Salafi reform movement (p. 2). Each of these factors is addressed in one chapter. The first chapter, “The Geographical and Ecological Background,” demonstrates how Najd’s geographical setting and climatic conditions (viz., a desert region with an unpredictable climate) dictated its people’s hard lifestyle and activities. For example, a persistant drought could turn a settlement, a region, or even the entire emirate into a wasteland (pp. 36-37). The second chapter, “An Historical Background,” surveys Najd’s inhabitants at the rise of Islam and follows its demographic and political developments throughout the first 9 centuries of the Islamic era. On the eve of Islam, Najd was populous and prosperous; however, by the third/ninth ...